2021
DOI: 10.5114/hpr.2021.105007
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 changes the motivation for physical activity participation: Polish-Chinese comparisons

Abstract: BackgroundCOVID-19 has brought people many negative emotions, such as fear and anxiety about the epidemic. However, when peo-ple in different countries face the COVID-19 epidemic, the impact is also different due to different cultural and sports hab-its. Therefore, this study compares China and Poland’s sports motivations in the face of COVID-19 anxiety to find out the cultural differences behind them.Participants and procedureIn the study were N = 674 participants (female n = 407, male n = 260, other n = 4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The Chinese government has implemented strict social distancing measures to curb the spread of COVID-19, such as shutting down non-essential businesses and public transport. Nevertheless, this popular measure not only brings great challenges and changes to people's daily life and social style but also has significant effects on people's physical and mental health [47]. Although the COVID-19 pandemic is a rare event, its impact may be printed on each individual concerned [48].…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese government has implemented strict social distancing measures to curb the spread of COVID-19, such as shutting down non-essential businesses and public transport. Nevertheless, this popular measure not only brings great challenges and changes to people's daily life and social style but also has significant effects on people's physical and mental health [47]. Although the COVID-19 pandemic is a rare event, its impact may be printed on each individual concerned [48].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the impact of the coronavirus 19 (COVID-19) outbreak is a problem that cannot be ignored. The COVID-19 outbreak threatened public physical health while having a profound impact on the public’s mental health ( 64 , 65 ). Indeed, several self-reported studies have suggested that dietary restrictions or compensatory behaviors were further exacerbated during the outbreak ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the current study shows, the probability of exercising is also linked to COVID-19 anxiety. In studies of Polish and Chinese respondents, Wilczyńska et al ( 2021 ) proved that fear of COVID-19 changes people’s motives to engage in PA and that these motives vary between women and men as well as among people of different ages. Additionally, the results of this study indicated that age was negatively related to PA among Orthodox Christians and Catholics and that gender was related to PA only among Sunni Muslims, also indicating that the probability of PA was higher among men, which is in contradiction with the results of many other studies showing a different approach to health-promoting physical activity based on gender (Pawłowska et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%